Activities of Daily Living Index in elderly patients with hypertension and frailty syndrome after non-ST segment elevation myocardial infarction - N. M. Agarkov; O. A. Osipova; S. N. Shurygin; L. V. Kolpina; V. I. Kolomiets (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To analyze Barthel Index of Activities of Daily Living (ADL) in elderly patients with hypertension (HTN) and frailty 6 months after non-ST segment elevation myocardial infarction non-STEMI).Material and methods. ADL was studied in 114 elderly patients (60-74 years old) with non-STEMI, HN and frailty and 80 patients of the same age with non-STEMI and HTN, but without frailty. ADL was determined 6 months after suffering non-STEMI.Results. ADL in patients with frailty was reduced to a greater extent (55,8 [52,4-57,9]) than in non-frail patients (72,9 [70,3-78,6]) (p<0,01). According to factor analysis, ADL reduction in frail patients compared with non-frail patients was mainly due to bed-chair transfer — 6,4 [6,2- 6,8] vs 9,8 [8,1-11,5] (p<0,001), walking test — 8,1 [8,0-8,5] vs 10,6 [9,4-12,7] (p<0,001), stair climbing — 5,3 [5,1-5,7] vs 7,4 [6,8-8,9] (p<0,001). ADL in patients with frailty and blood pressure (BP) <160/100 mm Hg was 62,1 [60,3-69,9], which is significantly higher than in frail patients with BP ≥160/100 mm Hg (48,0 [36,3-53,2]) (p<0,01).Conclusion. In frail patients aged 60-74 years, compared with non- frail patients, 6 months after non-STEMI, ADL was significantly lower in such components as stair climbing, walking, and bed-chair transfer. In patients with frailty and BP <160/100 mm Hg, ADL is significantly higher than in patients with higher blood pressure.